Entrepreneurship Education for Family Investment Values in Indonesia and the Philippines - Husin, Azizah; Yosef, Yosef; Asuan, Maria Elvira; Sumarni, Sri; Surino, Portio O; Dellomos, Carl O (Universitas Negeri Semarang, 2020)
Education at home is preparing a child for the future even though parents educate their child without a specific goal. But the child gets the knowledge, value, skills, and habits of parental education with love and compassion. The purpose of this research is to know the entrepreneurial education conducted by parents to children in Indonesia and the Philippines. The study was conducted in Indonesia and the Philippines. The population of this research comes from university students in Indonesia and the Philippines. The research respondent is the first semester student to become a respondent, as it is still heavily influenced by family education, the spread of questionnaires using Google forms, where the intended student is 2019 class students to fill the form provided. The maximum sample amount is determined, 216 respondents were acquired for each country. Data analysis techniques use percentages, data is outlined based on the educational aspect given to students by parents in the family. Shows that parents in Indonesia and the Philippines have done their job well. Indonesia acquires higher average value than the Philippines for all components, namely: knowledge, values, habits, and entrepreneurial skills. Overall, it looks how much the average acquisition shows the difference in the results of Indonesia and the Philippines in educating future entrepreneurs by parents. Habituation in children through assignments to do something at home or homework. The value of skills educated by parents in the form of leadership values and the ability to network, communicate, and make decisions quickly. Entrepreneurship education can provide an intensive investment value as long as the child is still in the educational process of his parents at home.